Mystus prabini, a new species of catfish (Siluriformes: Bagridae) from Arunachal Pradesh, north-eastern, India - Darshan, Achom; Abujam, Santoshkumar; Kumar, Ram; Parhi, Janmejay; Singh, Yambem Suresh; Vishwanath, Waikhom; Das, Debangshu Narayan; Pandey, Pramod Kumar (Zootaxa, 2019)
Mystus prabini, new species, is described from the Sinkin and the Dibang River in the Lower Dibang Valley District of Arunachal Pradesh, India. The new species differs from all South-Asian congeners except M. bleekeri, M. cavasius, M. zeylanicus, M. falcarius, M. seengtee, M. cineraceus, M. ngasep, M. rufescens and M. ankutta in having a long adipose fin that reaches anteriorly (vs. distinctly does not reach) the base of the last dorsal-fin ray. The new species can be distinguished from the named nine species in having (vs. lacking) a narrow black mid-lateral stripe extending from the anterior region of tympanic spot to the rounded black spot at the caudal-fin base. The analysis of mitochondrial cytochrome c oxidase subunit I (COI) gene sequence shows that the K2P value between Mystus prabini and all other Mystus species ranges from 8.6–22.1%. Mystus prabini is closest genetically to M. bleekeri and M. albolineatus, from which species it has a genetic distance of 8.6% and 13.9%, respectively. The genetic distance (K2P) between the new species and M. dibrugarensis is 21.1%.